The ESX/type VII secretion system modulates development, but not virulence, of the plant pathogen Streptomyces scabies. (26th September 2012) - Fyans, Joanna K.; Bignell, Dawn; Loria, Rosemary; Toth, Ian; Palmer, Tracy
Summary: Streptomyces scabies is a model organism for the investigation of plant–microbe interactions in Gram‐positive bacteria. Here, we investigate the type VII protein secretion system (T7SS) in S. scabies ; the T7SS is required for the virulence of other Gram‐positive bacteria, including Mycobacterium tuberculosis and Staphylococcus aureus . The hallmarks of a functional T7SS are an EccC protein that forms an essential component of the secretion apparatus and two small, sequence‐related substrate proteins, EsxA and EsxB. A putative transmembrane protein, EccD, may also be associated with T7S in Actinobacteria. In this study, we constructed strains of the plant pathogen S. scabies carrying marked mutations in genes coding for EccC, EccD, EsxA and EsxB. Unexpectedly, we showed that all four mutant strains retain full virulence towards several plant hosts. However, disruption of the esxA or esxB, but not eccC or eccD, genes affects S. scabies development, including a delay in sporulation, abnormal spore chains and resistance to lysis by the Streptomyces ‐specific phage ϕC31. We further showed that these phenotypes are specific to the loss of the T7SS substrate proteins EsxA and EsxB, and are not observed when components of the T7SS secretion machinery are lacking. Taken together, these results imply an unexpected intracellular role for EsxA and EsxB.